Oxygen assist in plasma arc cutting of 304 stainless steel sheets - Lew, Eng Choon. (2008)
This dissertation presents the results obtained from the study on plasma arc cutting with additional oxygen gas to support the combustion. Both the plasma arc cutting and oxyfuel cutting have been practised extensively in the metalwork industry. The objective of this study is to combine both processes so that the cutting performance can be improved. The experiments were carried out on Grade 304 (UNS no S30400) austenitic stainless steel sheets with a thickness of 1.0 mm.